Effects of diets, antimicrobials and minerals on the revalence and antimicrobial susceptibility of fecal bacteria in feedlot cattle - Jacob, Megan E (Kansas State University, 2007)
Antimicrobials are included in finishing cattle diets for growth promotion, feed efficiency, and protection against liver abscesses. The inclusion of in-feed antimicrobials at or below therapeutic concentrations may provide a selective pressure for antimicrobial resistant microorganisms. Additionally, heavy metals such as copper and zinc may be included in cattle diets because of growth-promoting effects. Heavy metal resistance genes are on transferable plasmids that also contain antimicrobial resistance genes. The objectives of this research were to 1) determine the prevalence of food-borne pathogens, Salmonella and E. coli O157, in cattle fed diets with or without monensin and tylosin and 0 or 25% wet corn distiller's grains (WDGS), 2) determine the prevalence of food-borne pathogens in cattle fed elevated concentrations of copper and zinc 3) evaluate the effect of antimicrobials on antimicrobial susceptibility of food-borne pathogens and commensal fecal bacteria, and 4) determine a possible association between in-feed antimicrobials and the concentration of antimicrobial resistance genes in the feces of cattle. Inclusion of 25% WDGS was associated with a higher prevalence of E. coli O157 on one of two sample collection days; however, there was no association between the use of monensin and tylosin, or copper and zinc on the prevalence of food-borne pathogens. Including monensin and tylosin in cattle diets was associated with an increased resistance of enterococci to macrolides, but was not related to concentration of the common macrolide resistance gene, ermB. In cattle fed diets with copper and/or zinc, no differences were observed in antimicrobial susceptibility or the concentration of antimicrobial resistance genes. In conclusion, results indicate that including growth-promoting antimicrobials in cattle diets at below therapeutic concentrations only limitedly impacted antimicrobial susceptibility and concentration of fecal antimicrobial resistance genes; however, this research encompassed only a select number of microorganisms. The positive association between WDGS and E. coli O157 prevalence in cattle has important implications for food safety, and warrants further investigation.
Keywords: Antimicrobial feed additives; Antimicrobial susceptibility; Distiller's grains; Cattle; Heavy metal resistance; Food-borne pathogens; Biology, Microbiology (0410); Biology, Veterinary Science (0778)